Analisis Yuridis Terkait Peran Tni Sebagai Pertahanan Keamanan Dan Bela Negara Dalam Menghadapi Kejahatan Siber - Nur Pratama, Daya; Triadi, Irwan (Journal Evidence Of Law, 2024)
This journal writing discusses the role of the TNI as a security defense and national defense in dealing with cyber crime in the digital era. This research aims to understand and analyze juridical analysis regarding the role of the TNI as a security defense and state defense in dealing with cyber crime. In writing this journal, we used a library approach research method which took as its basis the legislation in force in Indonesia and used a descriptive analysis method, namely by analyzing existing problems and the role of the Indonesian National Army as a security defense and state defense. The role of the Indonesian National Army (TNI) as a security defense and state defense in the face of cyber crime is emphasized in Law Number 34 of 2004 concerning the Indonesian National Army in chapter VI concerning the deployment and use of TNI forces. The TNI as a component of defense and security and state defense is correct in implementing existing regulations in Indonesia. However, the existence of cyber crimes that occurred in Indonesia has become an evaluation material to further improve military strategy in this case so that this conflict can be resolved quickly.